Analysis of the psychological path of merchants’ use of central bank digital currency: evidence from digital RMB - Zhu, Xiaoling; Zhu, Jianming (Frontiers in Blockchain, 2026)
Central Bank Digital Currency (CBDC) is emerging to disrupt existing payment monopolies and enhance digital-real economies integration, yet adoption barriers persist. This study investigates merchants’ willingness to adopt digital RMB(e-CNY) using the Technology-Organization-Environment (TOE) framework integrated with network effects. This study constructs a comprehensive model of e-CNY adoption, examining three key dimensions: technological adaptation, organizational support and environmental push, Structural Equation Modeling (SEM) and fuzzy set Qualitative Comparative Analysis (fsQCA) are applied to explore the complex interactions between these factors and merchants’ usage behavior. The findings reveal that high-frequency usage of e-CNY by merchants requires the synergistic interaction of technological, organizational and environmental factors, None of the individual factors—such as perceived comparative advantage, perceived ease of use, compatibility, management support, organizational resource and capability, policy support, or network effects—are necessary condition on their own. Three distinct paths to high-frequency e-CNY usage are identified: technology-enviroment driven, all-factor synergy and technology-driven, while a single path, the environmentally-deficient type, explains low-frequency usage. Based on these findings, the study proposes targeted policy recommendations to promot e-CNY adoption: enhance system compatibility, improve policy Incentives, develop network effects, and establish a feedback loop between policy–technology–behavior.